The Cemeteries and soils of Ayyubids : A Historical study - Salim Abdullah, Lolav (Humanities Journal of University of Zakho, 2021)
The death shrines and their places have key position in the Islamic society, hence the burial ground design is a significance issue in the Islamic community, as they have an effect on respecting the dead also their protecting from things harm them. This study is being allocated to shed lights on the historical study of the graves of the Ayyubid Kings in Egypt and sham area. Furthermore, it copes with several sections, together with the appearance of Islamic shrines and their improvement into the Ayyubid reign. This research explores the attention of Ayyubid Kings to graves, burial rituals also burial position, likewise, it examines the reason for electing the grave position of some Ayyubid Kings and the most well-known cemeteries in Egypt and sham in the Ayyubid century. It gives some details regarding to the Ayyubid, as some of the Ayyubid Kings selected the shrine, in addition the place where burial is intended for political and religious or otherwise. It clears up that some of the Ayyubid Kings suggested their good wills to their children as well as their grandchildren incidentally. Nonetheless, it depicts that when their desire was not met during their death to certain circumstance, whether military, political or other. As a result, it was postponed till conditions were in favor of it and their funeral was moved to the recommended position by the departed. It shows that the Ayyubid paid more attention to these graves in term of their design, writing and decorations. The type of script in which they wrote and their development all of these issue have major historical, artistic, social as well as traditional cultural.